Cultural Politics in the Transformation of Islamic Education in South Sumatra: A Study of the Pesantren Law 2019 - Kiki Mikail (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2022)
The relationship between the governing state officials and the ulama (Islamic scholars) governing pesantren (Islamic boarding schools) is mutually beneficial. One of the state’s accommodations regarding the pesantren’s interest and development is the formulation of legislation that provides a stronger acknowledgement and better legal foundation for the betterment of the pesantren, which is law number 18, 2019, concerning pesantren. The importance of this law and its relationship with the dynamics of Indonesian politics and Islamic education is still under study. Therefore, this article aims to unfold how Indonesian cultural politics engender the legislation of pesantren and whether such legislation positively impacts the betterment of the pesantren institution. Through qualitative research, this study found that the mutual relationship between the Indonesian government and Islamic learning institutions gives a conducive political and social environment for the formulation of the law regarding pesantren and the law strengthens the legitimacy of the pesantren in the Indonesian legal and educational system.